Zinc liquid / zinc vapor erosion resistant and thermal shock resistant refining furnace castable

CN122520442BActive Publication Date: 2026-10-23ANGANG IND GRP CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202610999397.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-07-07
Publication Date
2026-10-23
Estimated Expiration
2046-07-07

AI Technical Summary

Technical Problem

[0003]目前,熔析炉炉衬普遍采用高铝质、刚玉质或镁铬质耐火浇注料,但在实际应用中均存在以下技术缺陷,强度性能不足:常规浇注料拌合用水量偏高,制品气孔多、致密度低,常温抗压强度偏低,施工阶段易破损;抗锌液/锌蒸汽侵蚀能力弱:坯体连通孔隙多,锌液、锌蒸汽易渗入基体并发生化学反应,造成衬体粉化失效;抗热震性差,易产生贯穿性裂纹:刚玉质等高熔点浇注料脆性大、热膨胀系数高,在熔析炉频繁的冷热循环过程中,内部热应力无法有效释放,极易产生贯穿性裂纹,进一步加速锌液的渗透侵蚀,最终导致炉衬整体剥落失效

Benefits of technology

本发明的抗锌液/锌蒸汽侵蚀、抗热震性优良的熔析炉耐火浇注料,通过将板状刚玉颗粒、铬刚玉颗粒、铬刚玉细粉、α-氧化铝微粉、氧化锌预合成粉、镁铝尖晶石细粉以及硅微粉包覆改性高铝水泥加入强制式搅拌机中干混,加入不锈钢纤维和有机防爆纤维,继续干混,加入含氟聚醚水化调控致密助剂和去离子水,湿混,之后注到模具内,振动成型,成型后覆盖湿布,养护,脱模后进行烘烤,之后冷却,得到熔析炉耐火浇注料;含氟聚醚水化调控致密助剂不仅能降低浇注料加水量、改善施工流动性、提升常温与高温强度,更凭借氟碳键的优异耐高温性和疏水性,提高浇注料的高温强度保留率,并在内部形成疏水屏障,有效阻挡锌液与锌蒸汽的渗透侵蚀;硅微粉包覆改性高铝水泥通过核壳结构延缓水泥早期水化放热,避免快凝与温度开裂,延长施工窗口,后期硅微粉发挥火山灰活性填充孔隙、优化水化产物结构,进一步提升浇注料的致密度与抗热震性能;熔析炉耐火浇注料施工流动性好、强度保留率高,兼具优异的抗热震性与抗锌侵蚀性,可有效延长熔析炉炉衬的服役寿命。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure REF-OBJ-1782351906613-000001
    Figure REF-OBJ-1782351906613-000001
Patent Text Reader

Abstract

The present application relates to the field of refractory castable for fusing furnace, in particular to the refractory castable for fusing furnace with good resistance to zinc liquid / zinc vapor erosion and excellent thermal shock resistance, which is used to solve the problems of low normal temperature strength, poor resistance to zinc liquid and zinc vapor erosion and insufficient thermal shock resistance under cold and hot cycles of the existing refractory castable for fusing furnace; tabular corundum particles, chromium corundum particles, chromium corundum fine powder, alpha-alumina micropowder, zinc oxide pre-synthesized powder, magnesium-aluminum spinel fine powder and silicon micropowder coated modified high-alumina cement are dry mixed, stainless steel fibers and organic explosion-proof fibers are added and dry mixed, fluoride-containing polyether hydration control densification additives and deionized water are added and wet mixed, then the mixture is poured into a mold, cured, demolded and baked, cooled, and the refractory castable for fusing furnace is obtained; the refractory castable for fusing furnace has good construction fluidity, high strength retention rate, excellent thermal shock resistance and resistance to zinc liquid / zinc vapor erosion, and can effectively prolong the service life of the fusing furnace lining.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of refractory castables for melting furnaces, specifically to refractory castables for melting furnaces that exhibit excellent resistance to zinc liquid / zinc vapor erosion and thermal shock resistance. Background Technology

[0002] Zinc is an indispensable basic non-ferrous metal in the national economy, widely used in galvanizing for corrosion protection, alloy manufacturing, and new energy batteries. The melting and precipitation process, as the core technology for crude zinc refining, dominates the global zinc smelting industry due to its advantages of short process, low energy consumption, and simple operation. The melting and precipitation furnace is the core thermal equipment of this process. Its furnace lining operates under extremely harsh conditions, subjected to continuous erosion from high-temperature molten zinc and zinc vapor, as well as severe thermal shock loads from frequent start-ups and shutdowns. The service life of the furnace lining directly determines the production efficiency and operating costs of zinc smelting enterprises.

[0003] Currently, high-alumina, corundum, or magnesia-chromium refractory castables are commonly used for furnace linings in melting and precipitation furnaces. However, these castables all suffer from the following technical defects in practical applications: insufficient strength performance: conventional castables have a high water content in the mixing process, resulting in numerous pores, low density, and low compressive strength at room temperature, making them prone to breakage during construction; weak resistance to zinc liquid / zinc vapor erosion: the billet has many interconnected pores, allowing zinc liquid and zinc vapor to easily penetrate the matrix and undergo chemical reactions, causing the lining to pulverize and fail; poor thermal shock resistance, easily leading to through-cracks: high-melting-point castables such as corundum are brittle and have a high coefficient of thermal expansion. During the frequent hot and cold cycles in the melting and precipitation furnace, internal thermal stress cannot be effectively released, making it extremely easy to generate through-cracks, further accelerating the penetration and erosion of zinc liquid, and ultimately leading to the overall spalling and failure of the furnace lining.

[0004] Therefore, developing an environmentally friendly refractory castable for melting furnaces that can simultaneously achieve excellent strength performance, resistance to zinc liquid / zinc vapor erosion, and thermal shock resistance is a technical challenge that the zinc smelting industry urgently needs to solve. Summary of the Invention

[0005] In order to overcome the above-mentioned technical problems, the purpose of this invention is to provide a refractory castable for melting furnaces that is resistant to zinc liquid / zinc vapor erosion and has excellent thermal shock resistance.

[0006] The objective of this invention can be achieved through the following technical solutions: This application provides a refractory castable for melting furnaces that is resistant to zinc liquid / zinc vapor erosion and has excellent thermal shock resistance, comprising the following components in parts by weight: The composition includes 50-65 parts of tabular corundum particles, 10-20 parts of chromium corundum particles, 5-10 parts of chromium corundum fine powder, 3-8 parts of α-alumina micro powder, 2-5 parts of zinc oxide pre-synthesized powder, 2-5 parts of magnesium aluminum spinel fine powder, 3-6 parts of silica micropowder-coated modified high-alumina cement, 1.5-3 parts of stainless steel fiber, 0.05-0.15 parts of organic explosion-proof fiber, and 0.1-0.3 parts of fluorinated polyether hydration regulating densifying agent. The fluorinated polyether hydration-regulating densifying agent is prepared by the following steps: Step a1: Add dichloromethane, 1,4-butanediol, and the boron trifluoride diethyl ether complex to a three-necked flask equipped with a stirrer, thermometer, gas delivery tube, and constant-pressure dropping funnel. Purge with nitrogen for protection and stir the reaction at 20-25°C and a stirring rate of 300-400 r / min for 30-35 min. Then, transfer the three-necked flask to an ice bath at 0°C and continue stirring for 30-35 min. Add 2-[(2,2,2-trifluoroethoxy)methyl]ethylene oxide dropwise using the constant-pressure dropping funnel. After the addition is complete, maintain the temperature at a constant level. Stir the reaction for 12-13 hours, remove the ice bath, raise the temperature to room temperature, and continue stirring for another 12-13 hours. After the reaction is complete, add a dilute sodium bicarbonate aqueous solution to a three-necked flask, stir for 5-7 minutes, then transfer to a separatory funnel, discard the upper aqueous phase, wash and extract three times with saturated brine, collect the organic phase, add anhydrous sodium sulfate to the organic phase, dry at room temperature for 24-26 hours, filter, wash the filter cake three times with ethyl acetate, transfer the filtrate to a rotary evaporator, and rotary evaporate at a temperature of 35-40℃ to obtain hydroxyl-terminated fluorinated polyether. Step a2: Add hydroxyl-terminated fluorinated polyether, 1,2-dichloroethane, p-toluenesulfonic acid, and p-hydroxyanisole to a three-necked flask equipped with a stirrer, gas delivery tube, water separator, and condenser. Purge with nitrogen for protection and stir the reaction at 68-70℃ and a stirring rate of 300-400 r / min for 60-70 min. Add acrylic acid dropwise for ≥40 min. After the addition is complete, continue stirring for 60-70 min. Raise the temperature to 80-82℃ and stop the reaction when the liquid level in the water separator stops rising. Then, allow it to cool naturally to room temperature. Wash and extract three times with saturated sodium bicarbonate aqueous solution. Add anhydrous sodium sulfate to the organic phase and dry at room temperature for 24-26 h. Filter the mixture and wash the filter cake three times with ethyl acetate. Distill the filtrate under reduced pressure at 60-70℃ and a vacuum degree of -0.09 MPa to obtain the fluorinated polyether acrylate functional monomer. Step a3: Add methyl allyl alcohol polyoxyethylene ether and 52% of the total amount of deionized water to a four-necked flask equipped with a stirrer, a gas delivery tube, and two constant-pressure dropping funnels. Purge with nitrogen for protection and stir at a stirring rate of 300-400 r / min for 10-12 min. Then raise the temperature to 60℃. Mix and stir acrylic acid, sodium propylene sulfonate, fluorinated polyether acrylate functional monomers, and 35% of the total amount of deionized water, and transfer the mixture to constant-pressure dropping funnel A. Mix and stir ammonium persulfate, mercaptopropionic acid, and 13% of the total amount of deionized water, and transfer the mixture to constant-pressure dropping funnel B. Then add the mixture dropwise through both funnels simultaneously, with the total dropping time controlled at 3.5-4 h. After all the liquid has been added, continue stirring and reacting for 2.5-2.7 h. Then stop heating and allow it to cool naturally to room temperature. Add triethanolamine dropwise to adjust the pH to 6.0-7.0 to obtain the fluorinated polyether hydration regulating densifying agent.

[0007] In a preferred embodiment of the present invention, the ratio of dichloromethane, 1,4-butanediol, boron trifluoride diethyl ether complex, 2-[(2,2,2-trifluoroethoxy)methyl]ethylene oxide, and dilute sodium bicarbonate aqueous solution in step a1 is 50-60 mL : 2.1-2.5 mL : 1.20-1.44 mL : 115-138 g : 50-60 mL.

[0008] In a preferred embodiment of the present invention, the mass fraction of the dilute sodium bicarbonate aqueous solution in step a1 is 5%.

[0009] In a preferred embodiment of the present invention, the ratio of the amount of the hydroxyl-terminated fluorinated polyether, 1,2-dichloroethane, p-toluenesulfonic acid, p-hydroxyanisole and acrylic acid in step a2 is 75-150g: 25-50mL: 1-2g: 0.03-0.06g: 9-18g.

[0010] In a preferred embodiment of the present invention, the ratio of the amounts of methyl allyl alcohol polyoxyethylene ether, acrylic acid, sodium propylene sulfonate, fluorinated polyether acrylate functional monomer, ammonium persulfate, mercaptopropionic acid, and deionized water in step a3 is 70-105g: 8.4-12.6g: 4.5-6.8g: 4-6g: 0.8-1.2g: 0.85-1.28g: 152-228g.

[0011] In a preferred embodiment of the present invention, the methyl allyl alcohol polyoxyethylene ether in step a3 is of type HPEG-2400.

[0012] The silica fume-coated modified high-alumina cement is prepared by the following steps: Silica powder, dry polycarboxylate superplasticizer, and anhydrous ethanol were added to a beaker and ultrasonically dispersed for 15-17 minutes at a power of 200W to obtain a suspension. Then, high-alumina cement was added to a ball mill jar, followed by the suspension and zirconia grinding balls. The ball mill jar was sealed, and nitrogen was introduced to replace the air inside. The ball mill speed was set to 450 r / min, and the coating process was carried out for 45-50 minutes at a temperature of 25-30℃. After ball milling, the mixture was filtered, and the filter cake was washed 2-3 times with isopropanol. The filter cake was then dried in a vacuum drying oven at 105℃ for 4-6 hours, ground with an agate mortar, and passed through a 0.088 mm standard sieve to obtain silica powder-coated modified high-alumina cement.

[0013] In a preferred embodiment of the present invention, the ratio of the amount of silica powder, dry powder polycarboxylate superplasticizer, anhydrous ethanol and high-alumina cement is 1.5-1.7g: 0.15-0.17g: 150-170mL: 100-113g.

[0014] In a preferred embodiment of the present invention, the high-alumina cement and silica powder are dried in a vacuum drying oven at 105°C for 12 hours in advance and then cooled to room temperature before use.

[0015] In a preferred embodiment of the present invention, the silicon powder is active nano-silicon powder with SiO2 ≥ 99.0%, particle size ≤ 1 μm, and specific surface area ≥ 20 m². 2 / g.

[0016] In a preferred embodiment of the present invention, the high-alumina cement is of type CA80; and the dry powder polycarboxylate superplasticizer is of type Casstament®FS 30.

[0017] As a preferred embodiment of the present invention, a method for preparing a refractory castable for a melting furnace with excellent resistance to zinc liquid / zinc vapor erosion and thermal shock includes the following steps: Step 1: Weigh out 50-65 parts by weight of tabular corundum particles, 10-20 parts of chromium corundum particles, 5-10 parts of chromium corundum fine powder, 3-8 parts of α-alumina micro powder, 2-5 parts of zinc oxide pre-synthesized powder, 2-5 parts of magnesium aluminum spinel fine powder, 3-6 parts of silica micropowder-coated modified high-alumina cement, 1.5-3 parts of stainless steel fiber, 0.05-0.15 parts of organic explosion-proof fiber, and 0.1-0.3 parts of fluorinated polyether hydration regulating densifying agent, and set aside. Step 2: Add the tabular corundum particles, chromium corundum particles, chromium corundum fine powder, α-alumina micro powder, zinc oxide pre-synthesized powder, magnesium aluminum spinel fine powder, and silica micro powder-coated modified high-alumina cement to a forced mixer and dry mix for 1-2 minutes. Add stainless steel fibers and organic explosion-proof fibers, and continue dry mixing for 1-2 minutes. Add a fluorinated polyether hydration regulator and densifying agent and 5.5% (by weight of total materials) of deionized water, and wet mix for 3-5 minutes. Then pour the mixture into a mold and vibrate to form the final product. After removing air bubbles, the molded material is covered with a damp cloth and naturally cured at an environment above 20℃ for ≥36 hours. After demolding, it is baked by first heating from room temperature to 150℃ at a rate of 10-15℃ / h and holding for 8-12 hours, then heating to 300℃ at a rate of 5-10℃ / h and holding for 18-30 hours, and finally heating to 650℃ at a rate of 15-20℃ / h and holding for 8-12 hours. After that, it is naturally cooled to room temperature to obtain the refractory castable for the melting furnace.

[0018] In a preferred embodiment of the present invention, the tabular corundum particles have an Al2O3 content ≥99%, a SiO2 content ≤0.2%, and a Fe2O3 content ≤0.1%; the chromium corundum particles have an Al2O3 content ≥90%, a Cr2O3 content of 8-10%, a SiO2 content ≤0.3%, and a Fe2O3 content ≤0.2%; the chromium corundum fine powder has a particle size ≤0.044mm, an Al2O3 content ≥90%, and a Cr2O3 content of 8-10%; and the α-alumina micro powder has a particle size ≤5μm and an Al2O3 content ≥99%. 5%; the zinc oxide pre-synthesized powder has a ZnO content ≥99% and a particle size ≤0.074mm; the magnesium aluminum spinel fine powder has an MgO content of 20-25%, an Al2O3 content of 74-79%, and a particle size ≤0.074mm; the stainless steel fiber is 304 stainless steel fiber with a diameter of 0.1-0.2mm, a length of 10-20mm, and a heat resistance temperature ≥800℃; the organic explosion-proof fiber is polypropylene fiber with a length of 3-6mm; the zinc oxide pre-synthesized powder is a composite powder synthesized from zinc oxide, aluminum oxide, and magnesium oxide in a pre-high-temperature solid-phase state.

[0019] The beneficial effects of this invention are: The present invention relates to a refractory castable for melting furnaces with excellent resistance to zinc liquid / zinc vapor erosion and thermal shock. This is achieved by dry mixing plate-shaped corundum particles, chromium corundum particles, chromium corundum fine powder, α-alumina micro powder, zinc oxide pre-synthesized powder, magnesium aluminum spinel fine powder, and silica micro-powder-coated modified high-alumina cement in a forced mixer. Stainless steel fibers and organic explosion-proof fibers are then added, and the mixture is further dry-mixed. A fluorinated polyether hydration regulator and densifying agent, along with deionized water, are then added, and the mixture is wet-mixed. The mixture is then poured into a mold, vibrated to form, covered with a damp cloth, cured, demolded, baked, and then cooled to obtain the refractory castable for melting furnaces. The fluorinated polyether hydration regulator and densifying agent not only reduces the amount of water added to the castable but also improves the application properties. The high-alumina cement exhibits excellent workability and strength at both room and high temperatures. Furthermore, the superior high-temperature resistance and hydrophobicity of the fluorocarbon bonds enhance the high-temperature strength retention rate of the castable, while the internal hydrophobic barrier effectively prevents the penetration and erosion of molten zinc and zinc vapor. The silica-coated modified high-alumina cement, through its core-shell structure, delays early hydration heat release, preventing rapid setting and temperature cracking, and extending the construction window. Later, the silica powder utilizes its pozzolanic activity to fill pores and optimize the structure of hydration products, further improving the density and thermal shock resistance of the castable. This refractory castable for melting furnaces boasts good workability, high strength retention, and excellent thermal shock resistance and zinc corrosion resistance, effectively extending the service life of the melting furnace lining.

[0020] In the preparation of refractory castables for melting furnaces, a fluorinated polyether hydration-regulating densifying agent was first prepared. Using 2-[(2,2,2-trifluoroethoxy)methyl]ethylene oxide as a raw material, a ring-opening polymerization reaction was carried out with 1,4-butanediol under the catalysis of a boron trifluoride diethyl ether complex. The boron trifluoride diethyl ether complex, acting as a Lewis acid catalyst, activated the ethylene oxide ring, promoting its ring-opening and condensation with the hydroxyl groups of 1,4-butanediol, generating a linear fluorinated polyether with dual-terminated hydroxyl groups. The hydrophobic fluorine chain of the fluorinated polyether can reduce the surface tension of the molecule and enhance its adhesion to the surface of cement particles. The adsorption capacity enhances dispersion stability, and the terminal hydroxyl structure provides active sites for subsequent esterification reactions with acrylic acid, ensuring the integrity of the molecular structure. Subsequently, the terminal hydroxyl fluorinated polyether undergoes esterification with acrylic acid under the catalysis of p-toluenesulfonic acid, generating a fluorinated polyether acrylate functional monomer. Simultaneously, polymerizable carbon-carbon double bonds are introduced, providing active groups for subsequent polymerization reactions. The introduction of fluorinated polyether segments gives the monomer both hydrophobicity and steric hindrance effects, effectively inhibiting the agglomeration of cement particles. The carbon-carbon double bonds of the acrylate structure can participate in subsequent free radical polymerization. Then, methyl allyl alcohol polyoxyethylene... With ethylene ether as the main chain and acrylic acid, sodium propylene sulfonate, and fluorinated polyether acrylate functional monomers as side chain monomers, a free radical copolymerization reaction occurs under the action of ammonium persulfate initiator and mercaptopropionic acid chain transfer agent. Ammonium persulfate decomposes to generate free radicals to initiate polymerization, and mercaptopropionic acid controls the molecular weight through chain transfer, ultimately forming a fluorinated polyether hydration regulating densifying agent with a comb-like structure. The comb-like molecular structure of the main chain can provide steric hindrance, while the carboxyl and sulfonic acid groups of the side chains can provide electrostatic repulsion. The dual effect improves the dispersion effect of cement particles, and the fluorinated polyether side chains further enhance the anti-adsorption capacity of the molecules. This fluorinated polyether hydration regulating and densifying agent can uniformly disperse castable powder raw materials, optimize particle packing and arrangement, reduce the amount of water used in mixing the system, reduce internal interconnected pores after molding, regulate the hydration rate of high-alumina cement, promote the uniform growth of hydration products, increase the density of the green body, and significantly improve the mechanical strength of the castable at room temperature and high temperature. The fluorocarbon groups in the agent molecule can form a hydrophobic barrier layer on the inner wall of the matrix pores, preventing zinc liquid and zinc vapor from penetrating into the matrix. At the same time, the densified matrix structure can buffer thermal alternating stress, improve the thermal shock resistance of the material, reduce furnace lining cracking and spalling, and has wide applicability.

[0021] In the preparation of refractory castables for melting furnaces, a silica-coated modified high-alumina cement was prepared. First, silica powder, dry-powdered polycarboxylate superplasticizer, and anhydrous ethanol were mixed and ultrasonically dispersed. The polar groups such as carboxyl and sulfonic acid groups of the polycarboxylate superplasticizer adsorbed onto the surface of the silica powder through electrostatic attraction. Simultaneously, the non-polar side chains of the superplasticizer and the organic modified layer on the surface of the silica powder ensured uniform dispersion of the silica powder in the anhydrous ethanol, forming a stable suspension. The high-alumina cement and the silica powder suspension were then ball-milled together. The impact and grinding action of the zirconia grinding balls caused surface defects on the high-alumina cement particles. Microcracks increase the specific surface area. Under mechanical force, silica fume in the suspension adheres to the surface of high-alumina cement particles, forming a coating layer. The silica fume coating layer can delay the early hydration heat release of cement, avoid rapid setting and temperature cracking. In the later stage, the silica fume exerts pozzolanic activity, generating dense hydration products and filling pores. It can also improve the strength of castables at room temperature and high temperature. In addition, the dense core-shell structure reduces porosity, reduces the penetration of slag, alkali metals and acidic gases, and at the same time refines the grains to improve thermal shock resistance, reduce thermal cycling cracking and spalling, and extend the service life of the melting furnace lining. Detailed Implementation

[0022] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0023] Example 1:

[0024] This embodiment describes a method for preparing a refractory castable for a melting furnace that exhibits excellent resistance to zinc liquid / zinc vapor erosion and thermal shock, comprising the following steps: Step S1: Add 50 mL of dichloromethane, 2.1 mL of 1,4-butanediol, and 1.20 mL of boron trifluoride diethyl ether complex to a three-necked flask equipped with a stirrer, thermometer, gas delivery tube, and constant-pressure dropping funnel. Purge with nitrogen and stir for 30 min at 20°C and a stirring rate of 300 r / min. Then transfer the three-necked flask to a 0°C ice bath and continue stirring for 30 min. Finally, add 115 g of the mixture dropwise using the constant-pressure dropping funnel. 2-[(2,2,2-trifluoroethoxy)methyl]ethylene oxide was added dropwise, and the mixture was stirred at a constant temperature for 12 hours. The ice bath was removed, the mixture was brought to room temperature, and the stirring was continued for another 12 hours. After the reaction was completed, 50 mL of dilute sodium bicarbonate aqueous solution (5% by mass) was added to a three-necked flask and stirred for 5 minutes. The mixture was then transferred to a separatory funnel, the upper aqueous phase was discarded, and the mixture was washed and extracted three times with saturated saline solution. The organic phase was collected, anhydrous sodium sulfate was added to the organic phase, and the mixture was dried at room temperature for 24 hours. The mixture was then filtered, and the filter cake was washed three times with ethyl acetate. The filtrate was transferred to a rotary evaporator and evaporated at 35°C to obtain hydroxyl-terminated fluorinated polyether. Step S2: 75g of hydroxyl-terminated fluorinated polyether, 25mL of 1,2-dichloroethane, 1g of p-toluenesulfonic acid, and 0.03g of p-hydroxyanisole were added to a three-necked flask equipped with a stirrer, a gas delivery tube, a water separator, and a condenser. Nitrogen gas was introduced for protection, and the mixture was stirred at 68℃ and a stirring rate of 300r / min for 60min. 9g of acrylic acid was added dropwise over a period of ≥40min. After the addition was complete, the mixture was stirred for another 60min. The temperature was raised to 80℃, and the reaction was stopped when the liquid level in the water separator stopped rising. The mixture was then allowed to cool naturally to room temperature. It was washed and extracted three times with saturated sodium bicarbonate aqueous solution. Anhydrous sodium sulfate was added to the organic phase, and the mixture was dried at room temperature for 24h. The mixture was filtered, and the filter cake was washed three times with ethyl acetate. The filtrate was distilled under reduced pressure at 60℃ and a vacuum of -0.09MPa to obtain the fluorinated polyether acrylate functional monomer. Step S3: Add 70g of methyl allyl alcohol polyoxyethylene ether (model HPEG-2400) and 79g of deionized water to a four-necked flask equipped with a stirrer, a gas delivery tube, and two constant-pressure dropping funnels. Purge with nitrogen for protection and stir for 10 minutes at a stirring rate of 300 rpm. Then raise the temperature to 60°C and add 8.4g of acrylic acid, 4.5g of sodium propylene sulfonate, and 4g of fluorinated polyether acrylate functional monomers... Mix 53g of deionized water and stir, then transfer the mixture to a constant pressure dropping funnel A. Mix 0.8g of ammonium persulfate, 0.85g of mercaptopropionic acid, and 20g of deionized water and stir, then transfer the mixture to a constant pressure dropping funnel B. Add the mixture dropwise through both funnels simultaneously, with a total dropping time of 3.5 hours. After all the liquid has been added, continue stirring and reacting for another 2.5 hours. Then stop heating and allow the mixture to cool naturally to room temperature. Add triethanolamine to adjust the pH to 6.0 to obtain a fluorinated polyether hydration regulating densifying agent. Step S4: Add 1.5g of silicon micropowder (the silicon micropowder is pre-dried in a vacuum drying oven at 105℃ for 12 hours and then cooled to room temperature before use; the silicon micropowder is active nano-silicon micropowder, with SiO2 ≥ 99.0%, particle size ≤ 1μm, and specific surface area ≥ 20m²). 2 0.15 g of dry polycarboxylate superplasticizer (model: Casstament®FS 30) and 150 mL of anhydrous ethanol were added to a beaker and ultrasonically dispersed for 15 min at a power of 200 W to obtain a suspension. Then, 100 g of high alumina cement (model: CA80) was added to a ball mill jar, followed by the suspension and zirconia grinding balls (ball-to-material ratio: 10:1). The ball mill jar was sealed, and nitrogen was introduced to replace the air inside. The ball mill speed was set to 450 r / min, and the coating time was 45 min. The temperature was controlled at 25 °C. After ball milling, the mixture was filtered, and the filter cake was washed twice with isopropanol. The filter cake was then dried in a vacuum drying oven at 105 °C for 4 h, ground with an agate mortar, and passed through a 0.088 mm standard sieve to obtain silica-coated modified high alumina cement. Step S5: Weigh out 50 parts by weight of tabular corundum particles, 10 parts of chromium corundum particles, 5 parts of chromium corundum fine powder, 3 parts of α-alumina micro powder, 2 parts of zinc oxide pre-synthesized powder, 2 parts of magnesium aluminum spinel fine powder, 3 parts of silica micropowder coated modified high-alumina cement, 1.5 parts of stainless steel fiber, 0.05 parts of organic explosion-proof fiber, and 0.1 parts of fluorinated polyether hydration regulating densifying agent, and set aside. Step S6: Combine tabular corundum particles (Al2O3 content ≥99%, SiO2 content ≤0.2%, Fe2O3 content ≤0.1%), chromium corundum particles (Al2O3 content ≥90%, Cr2O3 content ≥8%, SiO2 content ≤0.3%, Fe2O3 content ≤0.2%), and chromium corundum fine powder (particle size ≤0.044mm, Al2O3 content ≥90%, Cr2O3 content ≤0.2%). 3. Al2O3 content 8%), α-alumina micro powder (α-alumina micro powder particle size ≤ 5μm, Al2O3 content ≥ 99.5%), zinc oxide pre-synthesized powder (zinc oxide pre-synthesized powder is a composite powder synthesized from zinc oxide, alumina, and magnesium oxide under high-temperature solid-state conditions; zinc oxide pre-synthesized powder ZnO content ≥ 99%, particle size ≤ 0.074mm), magnesium aluminum spinel fine powder (magnesium aluminum spinel fine powder MgO content 20%, Al2O3 content 79%, particle size ≤ 8%), α-alumina micro powder (α-alumina micro powder particle size ≤ 5μm, Al2O3 content ≥ 99.5%), MgO content ≥ 8%, Al2O3 content ≥ 99.5%, MgO content ≥ 99.5%, Al2O3 content ≥ 99.5%), MgO pre-synthesized powder is a composite powder synthesized from zinc oxide, alumina, and magnesium oxide under high-temperature solid-state conditions; MgO content ≥ 99.5%, Al2O3 content ≥ 99.5%, ...%, Al2O3 content ≥ 99.5%, Al2O3 content ≥ 99.5%, Al2O3 content ≥ Add 0.074mm) and silica-coated modified high-alumina cement to a forced mixer and dry mix for 1 minute. Add stainless steel fibers (304 stainless steel fibers, 0.1mm in diameter, 10mm in length, heat resistance ≥800℃) and organic explosion-proof fibers (organic explosion-proof fibers are polypropylene fibers, 3mm in length). Continue dry mixing for 1 minute. Add fluorinated polyether hydration regulator and densifying agent and 5.5% (by weight of total materials) of deionized water. Wet... Mix for 3 minutes, then pour into the mold, vibrate to form, remove air bubbles, cover with a damp cloth after forming, and cure naturally in an environment above 20℃ for ≥36 hours. After demolding, bake by first heating from room temperature to 150℃ at a heating rate of 10℃ / h and holding for 8 hours, then heating to 300℃ at a heating rate of 5℃ / h and holding for 18 hours, and finally heating to 650℃ at a heating rate of 15℃ / h and holding for 8 hours. After that, cool naturally to room temperature to obtain the refractory castable for melting furnace.

[0025] Example 2:

[0026] This embodiment describes a method for preparing a refractory castable for a melting furnace that exhibits excellent resistance to zinc liquid / zinc vapor erosion and thermal shock, comprising the following steps: Step S1: Add 55 mL of dichloromethane, 2.3 mL of 1,4-butanediol, and 1.20-1.44 mL of boron trifluoride diethyl ether complex to a three-necked flask equipped with a stirrer, thermometer, gas delivery tube, and constant-pressure dropping funnel. Purge with nitrogen and stir for 32 min at 23°C and a stirring rate of 350 r / min. Then, transfer the three-necked flask to a 0°C ice bath and continue stirring for 32 min. Finally, add 126 g of the mixture dropwise using the constant-pressure dropping funnel. 2-[(2,2,2-trifluoroethoxy)methyl]ethylene oxide was added dropwise, and the mixture was stirred at a constant temperature for 12.5 h. The ice bath was removed, the mixture was brought to room temperature, and the stirring was continued for another 12.5 h. After the reaction was completed, 55 mL of dilute sodium bicarbonate aqueous solution (5% by mass) was added to a three-necked flask, and the mixture was stirred for 6 min. The mixture was then transferred to a separatory funnel, the upper aqueous phase was discarded, and the mixture was washed and extracted three times with saturated brine. The organic phase was collected, anhydrous sodium sulfate was added to the organic phase, and the mixture was dried at room temperature for 25 h. The mixture was then filtered, and the filter cake was washed three times with ethyl acetate. The filtrate was transferred to a rotary evaporator and evaporated at 37 °C to obtain hydroxyl-terminated fluorinated polyether. Step S2: 112.5 g of hydroxyl-terminated fluorinated polyether, 37.5 mL of 1,2-dichloroethane, 1.5 g of p-toluenesulfonic acid, and 0.045 g of p-hydroxyanisole were added to a three-necked flask equipped with a stirrer, a gas delivery tube, a water separator, and a condenser. Nitrogen gas was introduced for protection, and the mixture was stirred at 69 °C and a stirring rate of 350 r / min for 65 min. 13.5 g of acrylic acid was added dropwise over a period of ≥40 min. After the addition was complete, the mixture was stirred for another 65 min. The temperature was raised to 81 °C, and the reaction was stopped when the liquid level in the water separator stopped rising. The mixture was then allowed to cool naturally to room temperature. The mixture was washed and extracted three times with saturated sodium bicarbonate aqueous solution. Anhydrous sodium sulfate was added to the organic phase, and the mixture was dried at room temperature for 25 h. The mixture was then filtered, and the filter cake was washed three times with ethyl acetate. The filtrate was distilled under reduced pressure at 65 °C and a vacuum of -0.09 MPa to obtain the fluorinated polyether acrylate functional monomer. Step S3: Add 87.5g of methyl allyl alcohol polyoxyethylene ether (model HPEG-2400) and 99g of deionized water to a four-necked flask equipped with a stirrer, a gas delivery tube, and two constant-pressure dropping funnels. Purge with nitrogen for protection and stir for 11 minutes at a stirring rate of 350 rpm. Then raise the temperature to 60°C and add 10.5g of acrylic acid, 5.65g of sodium propylene sulfonate, and 5g of fluorinated polyether acrylate. The monomer and 66g of deionized water were mixed and stirred, and then placed into a constant pressure dropping funnel A. 1g of ammonium persulfate, 1g of mercaptopropionic acid and 25g of deionized water were mixed and stirred, and then placed into a constant pressure dropping funnel B. The mixture was then added dropwise through both funnels simultaneously, with the total addition time controlled at 3.7h. After all the liquid was added, the reaction was stirred for another 2.6h. Then, heating was stopped, and the mixture was allowed to cool naturally to room temperature. Triethanolamine was added dropwise to adjust the pH to 6.5, thus obtaining a fluorinated polyether hydration regulating densifying agent. Step S4: Add 1.6g of silicon micropowder (the silicon micropowder is pre-dried in a vacuum drying oven at 105℃ for 12 hours and then cooled to room temperature before use; the silicon micropowder is active nano-silicon micropowder, with SiO2 ≥ 99.0%, particle size ≤ 1μm, and specific surface area ≥ 20m²). 2 0.16 g of dry polycarboxylate superplasticizer (model: Casstament®FS 30) and 160 mL of anhydrous ethanol were added to a beaker and ultrasonically dispersed for 16 min at a power of 200 W to obtain a suspension. Then, 106.5 g of high alumina cement (model: CA80) was added to a ball mill jar, followed by the suspension and zirconia grinding balls (ball-to-material ratio: 10:1). The ball mill jar was sealed, and nitrogen was introduced to replace the air inside. The ball mill speed was set to 450 r / min, and the coating time was 47 min. The temperature was controlled at 27 °C. After ball milling, the mixture was filtered, and the filter cake was washed twice with isopropanol. The filter cake was then dried in a vacuum drying oven at 105 °C for 5 h, ground with an agate mortar, and passed through a 0.088 mm standard sieve to obtain silica-coated modified high alumina cement. Step S5: Weigh out 57.5 parts by weight of tabular corundum particles, 15 parts of chromium corundum particles, 7.5 parts of chromium corundum fine powder, 5.5 parts of α-alumina micro powder, 3.5 parts of zinc oxide pre-synthesized powder, 3.5 parts of magnesium aluminum spinel fine powder, 4.5 parts of silica micropowder-coated modified high-alumina cement, 2.3 parts of stainless steel fiber, 0.1 parts of organic explosion-proof fiber, and 0.2 parts of fluorinated polyether hydration regulating densifying agent, and set aside for later use; Step S6: Combine tabular corundum particles (Al2O3 content ≥ 99%, SiO2 content ≤ 0.2%, Fe2O3 content ≤ 0.1%), chromium corundum particles (Al2O3 content ≥ 90%, Cr2O3 content ≤ 9%, SiO2 content ≤ 0.3%, Fe2O3 content ≤ 0.2%), and chromium corundum fine powder (particle size ≤ 0.044mm, Al2O3 content ≥ 90%, Cr2O3 content ≤ 0.2%). The following powders are used: α-alumina micro powder (particle size ≤ 5 μm, Al2O3 content ≥ 99.5%), zinc oxide pre-synthesized powder (a composite powder synthesized from zinc oxide, alumina, and magnesium oxide under high-temperature solid-state conditions, with ZnO content ≥ 99% and particle size ≤ 0.074 mm), and magnesium aluminum spinel fine powder (MgO content 23%, Al2O3 content 76%, particle size ≤ 0.07 mm). Add silica-coated modified high-alumina cement (4mm) and silica fume to a forced mixer and dry mix for 1.5 minutes. Add stainless steel fibers (304 stainless steel fibers, 0.1mm in diameter, 15mm in length, heat resistance ≥800℃) and organic explosion-proof fibers (organic explosion-proof fibers are polypropylene fibers, 4mm in length), and continue dry mixing for 1.5 minutes. Add fluorinated polyether hydration regulator and densifying agent and 5.5% (by weight of total materials) of deionized water, and wet mix for 4 minutes. After min, it is injected into the mold, vibrated to form, and air bubbles are removed. After forming, it is covered with a damp cloth and naturally cured in an environment above 20℃ for ≥36h. After demolding, it is baked. First, the temperature is increased from room temperature to 150℃ at a heating rate of 13℃ / h and held for 10h. Then, the temperature is increased to 300℃ at a heating rate of 7.5℃ / h and held for 24h. Finally, the temperature is increased to 650℃ at a heating rate of 17℃ / h and held for 10h. After that, it is naturally cooled to room temperature to obtain the refractory castable for melting furnace.

[0027] Example 3:

[0028] This embodiment describes a method for preparing a refractory castable for a melting furnace that exhibits excellent resistance to zinc liquid / zinc vapor erosion and thermal shock, comprising the following steps: Step S1: Add 60 mL of dichloromethane, 2.5 mL of 1,4-butanediol, and 1.44 mL of boron trifluoride diethyl ether complex to a three-necked flask equipped with a stirrer, thermometer, gas delivery tube, and constant-pressure dropping funnel. Purge with nitrogen and stir at 25°C and 400 rpm for 35 min. Then transfer the flask to a 0°C ice bath and continue stirring for 35 min. Finally, add 138 g of the mixture dropwise using the constant-pressure dropping funnel. 2-[(2,2,2-trifluoroethoxy)methyl]ethylene oxide was added dropwise, and the mixture was stirred at a constant temperature for 13 hours. The ice bath was removed, the mixture was brought to room temperature, and the stirring was continued for another 13 hours. After the reaction was completed, 60 mL of dilute sodium bicarbonate aqueous solution (5% by mass) was added to a three-necked flask and stirred for 7 minutes. The mixture was then transferred to a separatory funnel, the upper aqueous phase was discarded, and the mixture was washed and extracted three times with saturated brine. The organic phase was collected, anhydrous sodium sulfate was added to the organic phase, and the mixture was dried at room temperature for 26 hours. The mixture was then filtered, and the filter cake was washed three times with ethyl acetate. The filtrate was transferred to a rotary evaporator and evaporated at 40°C to obtain hydroxyl-terminated fluorinated polyether. Step S2: 150g of hydroxyl-terminated fluorinated polyether, 50mL of 1,2-dichloroethane, 2g of p-toluenesulfonic acid, and 0.06g of p-hydroxyanisole were added to a three-necked flask equipped with a stirrer, a gas delivery tube, a water separator, and a condenser. Nitrogen gas was introduced for protection, and the mixture was stirred at 70℃ and a stirring rate of 400r / min for 70min. 18g of acrylic acid was added dropwise over a period of ≥40min. After the addition was complete, the mixture was stirred for another 70min. The temperature was raised to 82℃, and the reaction was stopped when the liquid level in the water separator stopped rising. The mixture was then allowed to cool naturally to room temperature. The mixture was washed and extracted three times with saturated sodium bicarbonate aqueous solution. Anhydrous sodium sulfate was added to the organic phase, and the mixture was dried at room temperature for 26h. The mixture was then filtered, and the filter cake was washed three times with ethyl acetate. The filtrate was distilled under reduced pressure at 70℃ and a vacuum of -0.09MPa to obtain the fluorinated polyether acrylate functional monomer. Step S3: Add 105g of methyl allyl alcohol polyoxyethylene ether (model HPEG-2400) and 118g of deionized water to a four-necked flask equipped with a stirrer, a gas delivery tube, and two constant-pressure dropping funnels. Purge with nitrogen for protection and stir for 12 minutes at a stirring rate of 400 rpm. Then raise the temperature to 60°C and add 12.6g of acrylic acid, 6.8g of sodium propylene sulfonate, and 6g of fluorinated polyether acrylate functional monomer. Mix the solid with 80g of deionized water and stir. Transfer the mixture to a constant pressure dropping funnel A. Mix 1.2g of ammonium persulfate, 1.28g of mercaptopropionic acid, and 30g of deionized water and stir. Transfer the mixture to a constant pressure dropping funnel B. Then, add the solids simultaneously through both funnels. The total dropping time is controlled at 4 hours. After all the liquid has been added, continue stirring and reacting for 2.7 hours. Then, stop heating and allow the mixture to cool naturally to room temperature. Add triethanolamine to adjust the pH to 7.0 to obtain a fluorinated polyether hydration regulating densifying agent. Step S4: Add 1.7g of silicon micropowder (the silicon micropowder is pre-dried in a vacuum drying oven at 105℃ for 12 hours and then cooled to room temperature before use; the silicon micropowder is active nano-silicon micropowder, with SiO2 ≥ 99.0%, particle size ≤ 1μm, and specific surface area ≥ 20m²). 2 0.17 g of dry polycarboxylate superplasticizer (model: Casstament®FS 30) and 170 mL of anhydrous ethanol were added to a beaker and ultrasonically dispersed for 17 min at a power of 200 W to obtain a suspension. Then, 113 g of high alumina cement (model: CA80) was added to a ball mill jar, followed by the suspension and zirconia grinding balls (ball-to-material ratio: 10:1). The ball mill jar was sealed, and nitrogen was introduced to replace the air inside. The ball mill speed was set to 450 r / min, and the coating time was 50 min. The temperature was controlled at 30 °C. After ball milling, the mixture was filtered, and the filter cake was washed three times with isopropanol. The filter cake was then dried in a vacuum drying oven at 105 °C for 6 h, ground with an agate mortar, and passed through a 0.088 mm standard sieve to obtain silica-coated modified high alumina cement. Step S5: Weigh out 65 parts by weight of tabular corundum particles, 20 parts of chromium corundum particles, 10 parts of chromium corundum fine powder, 8 parts of α-alumina micro powder, 5 parts of zinc oxide pre-synthesized powder, 5 parts of magnesium aluminum spinel fine powder, 6 parts of silica micro powder coated modified high alumina cement, 3 parts of stainless steel fiber, 0.15 parts of organic explosion-proof fiber, and 0.3 parts of fluorinated polyether hydration regulating densifying agent, and set aside for later use; Step S6: Combine tabular corundum particles (Al2O3 content ≥ 99%, SiO2 content ≤ 0.2%, Fe2O3 content ≤ 0.1%), chromium corundum particles (Al2O3 content ≥ 90%, Cr2O3 content ≤ 10%, SiO2 content ≤ 0.3%, Fe2O3 content ≤ 0.2%), and chromium corundum fine powder (particle size ≤ 0.044mm, Al2O3 content ≥ 90%, Cr2O3 content ≤ 0.2%). 3. Al2O3 content 10%), α-alumina micro powder (α-alumina micro powder particle size ≤ 5μm, Al2O3 content ≥ 99.5%), zinc oxide pre-synthesized powder (zinc oxide pre-synthesized powder is a composite powder synthesized from zinc oxide, alumina, and magnesium oxide under high-temperature solid-state conditions; zinc oxide pre-synthesized powder ZnO content ≥ 99%, particle size ≤ 0.074mm), magnesium aluminum spinel fine powder (magnesium aluminum spinel fine powder MgO content 25%, Al2O3 content 79%, particle size ≤ 10%), α-alumina micro powder (α-alumina micro powder particle size ≤ 5μm, Al2O3 content ≥ 99.5%), MgO content ≥ ... Add 0.074mm) and silica-coated modified high-alumina cement to a forced mixer and dry mix for 2 minutes. Add stainless steel fibers (304 stainless steel fibers, 0.2mm in diameter, 20mm in length, heat resistance ≥800℃) and organic explosion-proof fibers (organic explosion-proof fibers are polypropylene fibers, 6mm in length). Continue dry mixing for 2 minutes. Add fluorinated polyether hydration regulator and densifying agent and 5.5% (by weight of total materials) of deionized water and wet mix. After 5 minutes, the mixture is poured into the mold, vibrated to form, and air bubbles are removed. After forming, it is covered with a damp cloth and naturally cured in an environment above 20℃ for ≥36 hours. After demolding, it is baked. First, the temperature is increased from room temperature to 150℃ at a rate of 15℃ / h and held for 12 hours. Then, the temperature is increased to 300℃ at a rate of 10℃ / h and held for 30 hours. Finally, the temperature is increased to 650℃ at a rate of 20℃ / h and held for 12 hours. After that, it is naturally cooled to room temperature to obtain the refractory castable for the melting furnace.

[0029] Comparative Example 1: This comparative example illustrates a method for preparing a refractory castable for melting furnaces that exhibits excellent resistance to zinc molten / zinc vapor erosion and thermal shock, comprising the following steps: Step S1: Weigh out 50 parts by weight of tabular corundum particles, 10 parts of chromium corundum particles, 5 parts of chromium corundum fine powder, 3 parts of α-alumina micro powder, 2 parts of zinc oxide pre-synthesized powder, 2 parts of magnesium aluminum spinel fine powder, 3 parts of high alumina cement, 1.5 parts of stainless steel fiber, 0.05 parts of organic explosion-proof fiber, and 0.1 parts of ordinary polycarboxylate superplasticizer, and set aside. Step S2: Combine tabular corundum particles (Al2O3 content ≥99%, SiO2 content ≤0.2%, Fe2O3 content ≤0.1%), chromium corundum particles (Al2O3 content ≥90%, Cr2O3 content 8%, SiO2 content ≤0.3%, Fe2O3 content ≤0.2%), chromium corundum fine powder (particle size ≤0.044mm, Al2O3 content ≥90%, Cr2O3 content 8%), and α-oxygen... Alumina micro powder (α-alumina micro powder with a particle size ≤5μm and Al2O3 content ≥99.5%), zinc oxide pre-synthesized powder (zinc oxide pre-synthesized powder is a composite powder synthesized from zinc oxide, alumina, and magnesium oxide in a high-temperature solid-state process, with a ZnO content ≥99% and a particle size ≤0.074mm), magnesium aluminum spinel fine powder (magnesium aluminum spinel fine powder with MgO content of 20%, Al2O3 content of 79%, and a particle size ≤0.074mm), and (high-alumina cement is prepared by pre-synthesizing at 105℃) Dry in a vacuum drying oven for 12 hours, cool to room temperature before use. Add the high-alumina cement (model CA80) to a forced mixer and dry mix for 1 minute. Add stainless steel fibers (304 stainless steel fibers, 0.1 mm in diameter, 10 mm in length, heat resistance ≥800℃) and organic explosion-proof fibers (organic explosion-proof fibers are polypropylene fibers, 3 mm in length). Continue dry mixing for 1 minute. Add ordinary polycarboxylate superplasticizer (model Subote PCA®-Ⅰ) and the amount of [unspecified ingredient] that constitutes the total material weight. Mix 5.5% deionized water for 3 minutes, then pour into a mold, vibrate to form, remove air bubbles, cover with a damp cloth, and cure naturally at ≥20℃ for ≥36 hours. After demolding, bake by first heating from room temperature to 150℃ at a rate of 10℃ / h and holding for 8 hours, then heating to 300℃ at a rate of 5℃ / h and holding for 18 hours, and finally heating to 650℃ at a rate of 15℃ / h and holding for 8 hours. After that, cool naturally to room temperature to obtain the refractory castable for the melting furnace.

[0030] Comparative Example 2: This comparative example illustrates a method for preparing a refractory castable for melting furnaces that exhibits excellent resistance to zinc molten / zinc vapor erosion and thermal shock, comprising the following steps: Step S1: Add 1.5g of silicon micropowder (the silicon micropowder is pre-dried in a vacuum drying oven at 105℃ for 12 hours and then cooled to room temperature before use; the silicon micropowder is active nano-silicon micropowder, with SiO2 ≥ 99.0%, particle size ≤ 1μm, and specific surface area ≥ 20m²). 20.15 g of dry polycarboxylate superplasticizer (model: Casstament®FS 30) and 150 mL of anhydrous ethanol were added to a beaker and ultrasonically dispersed for 15 min at a power of 200 W to obtain a suspension. Then, 100 g of high alumina cement (model: CA80) was added to a ball mill jar, followed by the suspension and zirconia grinding balls (ball-to-material ratio: 10:1). The ball mill jar was sealed, and nitrogen was introduced to replace the air inside. The ball mill speed was set to 450 r / min, and the coating time was 45 min. The temperature was controlled at 25 °C. After ball milling, the mixture was filtered, and the filter cake was washed twice with isopropanol. The filter cake was then dried in a vacuum drying oven at 105 °C for 4 h, ground with an agate mortar, and passed through a 0.088 mm standard sieve to obtain silica-coated modified high alumina cement. Step S2: Weigh out 50 parts by weight of tabular corundum particles, 10 parts of chromium corundum particles, 5 parts of chromium corundum fine powder, 3 parts of α-alumina micro powder, 2 parts of zinc oxide pre-synthesized powder, 2 parts of magnesium aluminum spinel fine powder, 3 parts of silica micro powder coated modified high-alumina cement, 1.5 parts of stainless steel fiber, 0.05 parts of organic explosion-proof fiber, and 0.1 parts of ordinary polycarboxylate superplasticizer, and set aside. Step S3: Combine tabular corundum particles (Al2O3 content ≥ 99%, SiO2 content ≤ 0.2%, Fe2O3 content ≤ 0.1%), chromium corundum particles (Al2O3 content ≥ 90%, Cr2O3 content ≤ 8%, SiO2 content ≤ 0.3%, Fe2O3 content ≤ 0.2%), and chromium corundum fine powder (particle size ≤ 0.044mm, Al2O3 content ≥ 90%, Cr2O3 content ≤ 0.2%). The following powders are used: α-alumina micro powder (particle size ≤ 5 μm, Al2O3 content ≥ 99.5%), zinc oxide pre-synthesized powder (a composite powder synthesized from zinc oxide, alumina, and magnesium oxide under high-temperature solid-state conditions, with ZnO content ≥ 99% and particle size ≤ 0.074 mm), and magnesium aluminum spinel fine powder (MgO content 20%, Al2O3 content 79%, particle size ≤ 0.074 mm). Add silica-coated modified high-alumina cement (mm) and silica fume-coated high-alumina cement to a forced mixer and dry mix for 1 minute. Add stainless steel fibers (304 stainless steel fibers, 0.1 mm in diameter, 10 mm in length, heat resistance ≥800℃) and organic explosion-proof fibers (organic explosion-proof fibers are polypropylene fibers, 3 mm in length), and continue dry mixing for 1 minute. Add ordinary polycarboxylate superplasticizer (model: Subote PCA®-Ⅰ) and 5.5% of deionized water by weight of total materials. Mix water and water for 3 minutes, then pour the mixture into the mold, vibrate to form, remove air bubbles, cover with a damp cloth after forming, and cure naturally in an environment above 20℃ for ≥36 hours. After demolding, bake the mixture by first heating it from room temperature to 150℃ at a rate of 10℃ / h and holding it for 8 hours, then heating it to 300℃ at a rate of 5℃ / h and holding it for 18 hours, and finally heating it to 650℃ at a rate of 15℃ / h and holding it for 8 hours. After that, let it cool naturally to room temperature to obtain the refractory castable for the melting furnace.

[0031] Comparative Example 3: This comparative example illustrates a method for preparing a refractory castable for melting furnaces that exhibits excellent resistance to zinc molten / zinc vapor erosion and thermal shock, comprising the following steps: Step S1: Add 50 mL of dichloromethane, 2.1 mL of 1,4-butanediol, and 1.20 mL of boron trifluoride diethyl ether complex to a three-necked flask equipped with a stirrer, thermometer, gas delivery tube, and constant-pressure dropping funnel. Purge with nitrogen and stir for 30 min at 20°C and a stirring rate of 300 r / min. Then transfer the three-necked flask to a 0°C ice bath and continue stirring for 30 min. Finally, add 115 g of the mixture dropwise using the constant-pressure dropping funnel. 2-[(2,2,2-trifluoroethoxy)methyl]ethylene oxide was added dropwise, and the mixture was stirred at a constant temperature for 12 hours. The ice bath was removed, the mixture was brought to room temperature, and the stirring was continued for another 12 hours. After the reaction was completed, 50 mL of dilute sodium bicarbonate aqueous solution (5% by mass) was added to a three-necked flask and stirred for 5 minutes. The mixture was then transferred to a separatory funnel, the upper aqueous phase was discarded, and the mixture was washed and extracted three times with saturated saline solution. The organic phase was collected, anhydrous sodium sulfate was added to the organic phase, and the mixture was dried at room temperature for 24 hours. The mixture was then filtered, and the filter cake was washed three times with ethyl acetate. The filtrate was transferred to a rotary evaporator and evaporated at 35°C to obtain hydroxyl-terminated fluorinated polyether. Step S2: 75g of hydroxyl-terminated fluorinated polyether, 25mL of 1,2-dichloroethane, 1g of p-toluenesulfonic acid, and 0.03g of p-hydroxyanisole were added to a three-necked flask equipped with a stirrer, a gas delivery tube, a water separator, and a condenser. Nitrogen gas was introduced for protection, and the mixture was stirred at 68℃ and a stirring rate of 300r / min for 60min. 9g of acrylic acid was added dropwise over a period of ≥40min. After the addition was complete, the mixture was stirred for another 60min. The temperature was raised to 80℃, and the reaction was stopped when the liquid level in the water separator stopped rising. The mixture was then allowed to cool naturally to room temperature. It was washed and extracted three times with saturated sodium bicarbonate aqueous solution. Anhydrous sodium sulfate was added to the organic phase, and the mixture was dried at room temperature for 24h. The mixture was filtered, and the filter cake was washed three times with ethyl acetate. The filtrate was distilled under reduced pressure at 60℃ and a vacuum of -0.09MPa to obtain the fluorinated polyether acrylate functional monomer. Step S3: Add 70g of methyl allyl alcohol polyoxyethylene ether (model HPEG-2400) and 152g of 52% deionized water to a four-necked flask equipped with a stirrer, a gas delivery tube, and two constant-pressure dropping funnels. Purge with nitrogen for protection and stir for 10 minutes at a stirring rate of 300 rpm. Then raise the temperature to 60°C and add 8.4g of acrylic acid, 4.5g of sodium propylene sulfonate, and 4g of fluorinated polyether acrylate functional monomers... Mix 0.8g of ammonium persulfate, 0.85g of mercaptopropionic acid, and 13% of deionized water (total amount) into a constant pressure dropping funnel A. Mix and stir the mixture into a constant pressure dropping funnel B. Then, add the mixture dropwise through both funnels simultaneously. The total dropping time is controlled at 3.5h. After all the liquid has been added, continue stirring and reacting for 2.5h. Then, stop heating and allow it to cool naturally to room temperature. Add triethanolamine to adjust the pH to 6.0 to obtain a fluorinated polyether hydration regulating densifying agent. Step S4: Weigh out 50 parts by weight of tabular corundum particles, 10 parts of chromium corundum particles, 5 parts of chromium corundum fine powder, 3 parts of α-alumina micro powder, 2 parts of zinc oxide pre-synthesized powder, 2 parts of magnesium aluminum spinel fine powder, 3 parts of high alumina cement, 1.5 parts of stainless steel fiber, 0.05 parts of organic explosion-proof fiber, and 0.1 parts of fluorinated polyether hydration regulating densifying agent, and set aside for later use; Step S5: Combine tabular corundum particles (Al2O3 content ≥99%, SiO2 content ≤0.2%, Fe2O3 content ≤0.1%), chromium corundum particles (Al2O3 content ≥90%, Cr2O3 content 8%, SiO2 content ≤0.3%, Fe2O3 content ≤0.2%), chromium corundum fine powder (particle size ≤0.044mm, Al2O3 content ≥90%, Cr2O3 content 8%), α- Alumina micro powder (α-alumina micro powder with a particle size ≤5μm and Al2O3 content ≥99.5%), zinc oxide pre-synthesized powder (zinc oxide pre-synthesized powder is a composite powder synthesized from zinc oxide, alumina, and magnesium oxide under high-temperature solid-state conditions, with ZnO content ≥99% and particle size ≤0.074mm), magnesium aluminum spinel fine powder (magnesium aluminum spinel fine powder with MgO content of 20%, Al2O3 content of 79%, and particle size ≤0.074mm), and high-alumina cement (high-alumina cement is... Pre-dry in a vacuum drying oven at 105℃ for 12 hours, cool to room temperature before use. Add the high-alumina cement (model CA80) to a forced mixer and dry mix for 1 minute. Add stainless steel fibers (304 stainless steel fibers, 0.1mm in diameter, 10mm in length, heat resistance ≥800℃) and organic explosion-proof fibers (organic explosion-proof fibers are polypropylene fibers, 3mm in length). Continue dry mixing for 1 minute. Add a fluorinated polyether hydration regulator and densifying agent, accounting for 5% of the total material weight. Mix 0.5% deionized water for 3 minutes, then pour into a mold, vibrate to form, remove air bubbles, cover with a damp cloth after forming, and cure naturally in an environment above 20℃ for ≥36 hours. After demolding, bake by first heating from room temperature to 150℃ at a heating rate of 10℃ / h and holding for 8 hours, then heating to 300℃ at a heating rate of 5℃ / h and holding for 18 hours, and finally heating to 650℃ at a heating rate of 15℃ / h and holding for 8 hours. After that, cool naturally to room temperature to obtain the refractory castable for melting furnace.

[0032] Performance testing: The refractory castables for melting furnaces in Examples 1-3 and Comparative Examples 1-3 were tested according to the following methods; Initial flowability and 1-hour flowability retention rate test: The preparation methods of the melt-melting furnace refractory castables in Examples 1-3 and Comparative Examples 1-3 were followed by wet mixing before testing. Initial flowability test: A truncated conical mold (upper diameter 70mm, lower diameter 100mm, height 60mm) was placed in the center of a glass plate on a rammed table. The mold was moistened with a damp cloth. The mixed castable was poured into the mold in two layers. The first layer was filled to 2 / 3 of the mold height. A knife was used to make 15 vertical cuts, followed by 15 uniform tamping cuts from the edge to the center with a tamping rod. The second layer was filled to approximately 20mm above the mold opening. mm, scratch and tamp 10 times, scrape off excess material, smooth the surface, lift the round mold vertically, start the jumping table, and jump 25 times at a frequency of 1 time per second. Use calipers to measure the maximum diameter of the flowing part in two mutually perpendicular directions, and take the average value as the initial flowability (mm); 1h flowability retention rate test: put the remaining casting material into a sealed container, place it in a 20℃ environment and let it stand. After standing for 1 hour, stir the material again for 1 minute, repeat the above steps to test the flowability. 1h flowability retention rate = (1h flowability / initial flowability) × 100%.

[0033] Room temperature compressive strength test: Take a 40mm×40mm×160mm prism specimen and place it in the center of the pressure plate of the compression testing machine, making the pressure surface of the specimen perpendicular to the forming surface. Apply a uniform load at a rate of 1.0MPa / s until the specimen fails. Record the maximum failure load (N). Compressive strength (MPa) = maximum failure load (N) / pressure area (1600mm²) 2 ).

[0034] Post-firing compressive strength test: Take the prepared 40mm×40mm×160mm prism sample and put it into a high-temperature resistance furnace with a gap of more than 10mm between the samples. Heat it to 1100℃ at a rate of 5℃ / min, hold it at that temperature for 3 hours, turn off the power, and let it cool naturally to room temperature with the furnace. Test the compressive strength of the post-firing sample according to the above method for room temperature compressive strength.

[0035] Thermal shock resistance test: Take a 40mm×40mm×160mm prism sample, heat the high temperature furnace to 1100℃ and hold for 30min, quickly put the sample into the furnace, so that the center of the sample is located in the constant temperature zone of the furnace, hold for 15min, quickly take out the sample with clamps, and immediately immerse it vertically into flowing room temperature water to a depth of 50mm, hold for 3min, take out the sample, air dry for 5min, check whether the sample has broken or cracked, repeat the above cycle until the sample breaks, and record the number of thermal shock cycles of the sample.

[0036] Zinc liquid corrosion resistance test: Take a cylindrical crucible sample with an outer diameter of 50 mm, an inner diameter of 30 mm, and a height of 50 mm. Add 30 g of pure zinc ingot with a purity of ≥99.99% into the crucible. Cover the surface with 1 mm thick graphite powder to prevent the zinc liquid from oxidizing and volatilizing at high temperature. Place the crucible in a resistance furnace and heat it to 450°C at a rate of 5°C / min. Hold it at this temperature for 72 h. Turn off the power and allow it to cool naturally to room temperature with the furnace. Use a diamond cutter to cut the crucible symmetrically along the longitudinal direction. Use vernier calipers to measure the deepest corrosion depth of the inner wall of the crucible and the zinc liquid penetration depth (the maximum depth of the area with obvious color change).

[0037] The test results are shown in Table 1: Table 1: Test Results Summary Table

[0038] Referring to Table 1, based on the comparison between Examples 1-3 and Comparative Examples 1-3, it can be seen that the refractory castable for melting furnaces has been significantly improved in terms of workability, high-temperature strength, thermal shock resistance and zinc liquid corrosion resistance, fully meeting the stringent requirements for long-term service of melting furnaces.

[0039] Based on the comparison between Example 1 and Comparative Example 1, it can be seen that the simultaneous use of fluorinated polyether hydration regulating densification agent and silica powder coated modified high-alumina cement is the core of the excellent comprehensive performance of this castable. The synergistic effect of the two can comprehensively improve the workability, mechanical strength, thermal shock resistance and zinc liquid corrosion resistance of the material.

[0040] Based on the comparison between Example 1 and Comparative Example 2, it can be seen that the fluorinated polyether hydration regulating densifying agent can further improve the slump retention and workability of castables compared with commercially available ordinary polycarboxylate superplasticizers, while significantly improving the high-temperature mechanical properties, thermal shock resistance and zinc liquid corrosion resistance of the material.

[0041] Based on the comparison between Example 1 and Comparative Example 3, it can be seen that silica-coated modified high-alumina cement can further optimize the workability of castables compared with unmodified high-alumina cement, while improving the mechanical strength, thermal shock resistance and zinc liquid corrosion resistance of the material.

[0042] In the description of this specification, references to terms such as "an embodiment," "example," "specific example," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the invention. In this specification, illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.

[0043] The above description is merely an example and illustration of the present invention. Those skilled in the art can make various modifications or additions to the specific embodiments described or use similar methods to replace them, as long as they do not deviate from the invention or exceed the scope defined in this application, they should all fall within the protection scope of the present invention.

Claims

1. A refractory castable for melting furnaces with excellent resistance to zinc liquid / zinc vapor erosion and thermal shock, characterized in that, Includes the following components by weight: The composition includes 50-65 parts of tabular corundum particles, 10-20 parts of chromium corundum particles, 5-10 parts of chromium corundum fine powder, 3-8 parts of α-alumina micro powder, 2-5 parts of zinc oxide pre-synthesized powder, 2-5 parts of magnesium aluminum spinel fine powder, 3-6 parts of silica micropowder-coated modified high-alumina cement, 1.5-3 parts of stainless steel fiber, 0.05-0.15 parts of organic explosion-proof fiber, and 0.1-0.3 parts of fluorinated polyether hydration regulating densifying agent. The fluorinated polyether hydration-regulating densifying agent is prepared by the following steps: Step a1: Mix dichloromethane, 1,4-butanediol and boron trifluoride diethyl ether complex, stir and react, add 2-[(2,2,2-trifluoroethoxy)methyl]ethylene oxide dropwise, stir and react, then add dilute sodium bicarbonate aqueous solution and stir, then wash, extract, dry, filter, wash, and rotary evaporate to obtain hydroxyl-terminated fluorinated polyether. Step a2: Mix hydroxyl-terminated fluorinated polyether, 1,2-dichloroethane, p-toluenesulfonic acid and p-hydroxyanisole, stir and react, add acrylic acid dropwise and continue stirring, then cool, wash and extract, then dry, filter, wash, and distill under reduced pressure to obtain fluorinated polyether acrylate functional monomer. Step a3: Mix methyl allyl alcohol polyoxyethylene ether and 52% of the total amount of deionized water, stir, and then heat. Mix acrylic acid, sodium propylene sulfonate, fluorinated polyether acrylate functional monomer and 35% of the total amount of deionized water, stir, and pour into constant pressure dropping funnel A. Mix ammonium persulfate, mercaptopropionic acid and 13% of the total amount of deionized water, stir, and pour into constant pressure dropping funnel B. Then add the mixture dropwise through both funnels simultaneously, continue stirring the reaction, cool down, and adjust the pH to obtain the fluorinated polyether hydration regulating densifying agent.

2. The refractory castable for melting furnaces with excellent resistance to zinc liquid / zinc vapor erosion and thermal shock resistance according to claim 1, characterized in that, The ratio of dichloromethane, 1,4-butanediol, boron trifluoride diethyl ether complex, 2-[(2,2,2-trifluoroethoxy)methyl]ethylene oxide, and dilute sodium bicarbonate aqueous solution in step a1 is 50-60 mL. 2.1-2.5 mL: 1.20-1.44 mL: 115-138 g: 50-60 mL; the mass fraction of the dilute sodium bicarbonate aqueous solution is 5%.

3. The refractory castable for melting furnaces with excellent resistance to zinc liquid / zinc vapor erosion and thermal shock resistance according to claim 1, characterized in that, The ratio of the amount of hydroxyl-terminated fluorinated polyether, 1,2-dichloroethane, p-toluenesulfonic acid, p-hydroxyanisole, and acrylic acid used in step a2 is 75-150g: 25-50mL: 1-2g: 0.03-0.06g: 9-18g.

4. The refractory castable for melting furnaces with excellent resistance to zinc liquid / zinc vapor erosion and thermal shock resistance according to claim 1, characterized in that, The ratio of the amounts of methyl allyl alcohol polyoxyethylene ether, acrylic acid, sodium propylene sulfonate, fluorinated polyether acrylate functional monomer, ammonium persulfate, mercaptopropionic acid, and deionized water in step a3 is 70-105g: 8.4-12.6g: 4.5-6.8g: 4-6g: 0.8-1.2g: 0.85-1.28g: 152-228g.

5. The refractory castable for melting furnaces with excellent resistance to zinc liquid / zinc vapor erosion and thermal shock resistance according to claim 1, characterized in that, The silica fume-coated modified high-alumina cement is prepared by the following steps: Silica powder, dry polycarboxylate superplasticizer, and anhydrous ethanol were added to a beaker and ultrasonically dispersed to obtain a suspension. Then, high-alumina cement was added to a ball mill jar, followed by the suspension, and then zirconia grinding balls were added for coating. After that, the mixture was filtered, washed, dried, ground, and sieved to obtain silica powder-coated modified high-alumina cement.

6. The refractory castable for melting furnaces with excellent resistance to zinc liquid / zinc vapor erosion and thermal shock resistance according to claim 5, characterized in that, The ratio of the amount of silica powder, dry polycarboxylate superplasticizer, anhydrous ethanol and high-alumina cement is 1.5-1.7g: 0.15-0.17g: 150-170mL: 100-113g.

7. The refractory castable for melting furnaces with excellent resistance to zinc liquid / zinc vapor erosion and thermal shock resistance according to claim 5, characterized in that, The high-alumina cement and silica powder were dried in a vacuum drying oven at 105℃ for 12 hours before use and then cooled to room temperature.

8. The refractory castable for melting furnaces with excellent resistance to zinc liquid / zinc vapor erosion and thermal shock resistance according to claim 5, characterized in that, The silicon powder is active nano-silicon powder with SiO2 ≥ 99.0%, particle size ≤ 1 μm, and specific surface area ≥ 20 m². 2 / g.

9. The refractory castable for melting furnaces with excellent resistance to zinc liquid / zinc vapor erosion and thermal shock resistance according to claim 1, characterized in that, The preparation method of the refractory castable for the melting furnace includes the following steps: Step 1: Weigh out 50-65 parts by weight of tabular corundum particles, 10-20 parts of chromium corundum particles, 5-10 parts of chromium corundum fine powder, 3-8 parts of α-alumina micro powder, 2-5 parts of zinc oxide pre-synthesized powder, 2-5 parts of magnesium aluminum spinel fine powder, 3-6 parts of silica micropowder-coated modified high-alumina cement, 1.5-3 parts of stainless steel fiber, 0.05-0.15 parts of organic explosion-proof fiber, and 0.1-0.3 parts of fluorinated polyether hydration regulating densifying agent, and set aside. Step 2: Add tabular corundum particles, chromium corundum particles, chromium corundum fine powder, α-alumina micro powder, zinc oxide pre-synthesized powder, magnesium aluminum spinel fine powder, and silica micro powder-coated modified high-alumina cement to a forced mixer for dry mixing. Add stainless steel fiber and organic explosion-proof fiber, continue dry mixing, add fluorinated polyether hydration regulator and densification aid and deionized water, wet mix, then pour into a mold, cover with a damp cloth after molding, cure, demold, bake, and then cool to obtain the refractory castable for melting furnace.

10. The refractory castable for melting furnaces with excellent resistance to zinc liquid / zinc vapor erosion and thermal shock resistance according to claim 9, characterized in that, The tabular corundum particles have an Al2O3 content ≥99%, SiO2 content ≤0.2%, and Fe2O3 content ≤0.1%; the chromium corundum particles have an Al2O3 content ≥90%, Cr2O3 content 8-10%, SiO2 content ≤0.3%, and Fe2O3 content ≤0.2%; the chromium corundum fine powder has a particle size ≤0.044mm, an Al2O3 content ≥90%, and Cr2O3 content 8-10%; the α-alumina micro powder has a particle size ≤5μm and an Al2O3 content ≥99.5%; the oxide The zinc pre-synthesized powder has a ZnO content ≥99% and a particle size ≤0.074mm; the magnesium aluminum spinel fine powder has an MgO content of 20-25%, an Al2O3 content of 74-79%, and a particle size ≤0.074mm; the stainless steel fiber is 304 stainless steel fiber with a diameter of 0.1-0.2mm, a length of 10-20mm, and a heat resistance temperature ≥800℃; the organic explosion-proof fiber is polypropylene fiber with a length of 3-6mm; the zinc oxide pre-synthesized powder is a composite powder synthesized from zinc oxide, aluminum oxide, and magnesium oxide in a high-temperature solid-phase state.

Citation Information

Patent Citations

  • Anti-seepage cement mortar and preparation process thereof

    CN112537923A

  • MANUFACTURING METHOD OF REFRACTORY MASS

    RU2007101113A